Effect of Surrounding Texture on the Pursuit-Pursuing Illusion. (February 2014) - Bai, Yuanyuan; Ito, Hiroyuki
The pursuit-pursuing illusion is a visual illusion where a circular object placed in the centre of a radial pattern consisting of thin sectors is seen to move in the pursuit eye movement direction. The present study investigates the role of the surrounding texture, replacing the sectors with random dots or stripes in an orientation that was orthogonal, parallel or oblique to the pursuit direction. The experiments demonstrate that the acquired illusory effect was large for the orthogonal stripes. However, each surrounding texture produces a relatively smaller effect than the radial sectors. These results suggest that a hypothesis based on the property of a centre-surround relative-motion detector cannot fully explain the illusion and that the radial stimulus structure itself plays an important role in this illusion.